Developing young athletes at Qatar's ASPIRE Academy - Iwan, R. (New Studies in Athletics, 2009)
The success of 17 year-old Mahamad AI-Mannai (QAT), who won the silver medal in the octathlon with a score of 6,232 points at the 6th IAAF World Youth Championships in Bressanone, Italy, in July 2009, may have come as a surprise to some observers. But for the author, it was the product of a systematic programme of talent identification and development at the ASPIRE Academy for Sports Excellence in Doha, Qatar. Six ASPIRE athletes competed in Bressanone and all achieved new personal bests in their events. In a follow-up to an article, published in NSA in 2008, that described the talent identification procedures used at ASPIRE, the author shows how the academy's talent development programme works with special reference to the sport of athletics. He gives an overview of each of the programme's six pillars: 1) Introduction Phase, 2) Long-Term Athlete Development & Career Plan, 3) Monitoring Performance, 4) Sport Education, 5) Training Camps and 6) Competition Camps with additional information on AI-Manai's experience. He concludes with the points that AI-Mannai, who has trained on a regular basis over a period of four years, has an excellent basis for further performance improvement and will face a critical stage, when he graduates from,ASPIRE in 2011.